Young workers today: education, profession, social health - David L. Konstantinovskiy; Elena D. Voznesenskaya; Galina A. Cherednichenko (Социологическая наука и социальная практика, 2013)
The features of educational and professional trajectories of young workers, their orientations in the working activity, purposes about education and profession, ideas of the worker’s status are considered on the data of quantitative and qualitative sociological researches conducted at Russian industrial enterprises.